2020
DOI: 10.26508/lsa.201900499
|View full text |Cite
|
Sign up to set email alerts
|

Altering microtubule dynamics is synergistically toxic with spindle assembly checkpoint inhibition

Abstract: Chromosomal instability (CIN) and aneuploidy are hallmarks of cancer. As most cancers are aneuploid, targeting aneuploidy or CIN may be an effective way to target a broad spectrum of cancers. Here, we perform two small molecule compound screens to identify drugs that selectively target cells that are aneuploid or exhibit a CIN phenotype. We find that aneuploid cells are much more sensitive to the energy metabolism regulating drug ZLN005 than their euploid counterparts. Furthermore, cells with an ongoing CIN ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…Importantly, we found that the increased dependency of aneuploid cells on KIF18A is functionally related to their sensitivity to SAC inhibition. In line with our results, a recent study reported that altering microtubule polymerization rates synergized with SAC inhibition in blocking cell proliferation 65 , and a parallel study indicates that a loss of KIF18A activity, which alters microtubule polymerization rates within the spindle, leads to extended mitotic delays, multipolar spindles, and reduced proliferation in aneuploid cells (Stumpff lab; unpublished data). An important question remains what selective advantage is provided to aneuploid cells by downregulation of KIF18A.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, we found that the increased dependency of aneuploid cells on KIF18A is functionally related to their sensitivity to SAC inhibition. In line with our results, a recent study reported that altering microtubule polymerization rates synergized with SAC inhibition in blocking cell proliferation 65 , and a parallel study indicates that a loss of KIF18A activity, which alters microtubule polymerization rates within the spindle, leads to extended mitotic delays, multipolar spindles, and reduced proliferation in aneuploid cells (Stumpff lab; unpublished data). An important question remains what selective advantage is provided to aneuploid cells by downregulation of KIF18A.…”
Section: Discussionsupporting
confidence: 91%
“…To resolve this conundrum, we turned to isogenic models of TP53-WT near-diploid cells and their highly-aneuploid derivatives, based on HCT116, a chromosomally-stable, near-diploid human colon cancer cell line 54 , and RPE1, a chromosomally-stable, neardiploid non-transformed human retinal epithelial cell line 55 , that are commonly used to study the cellular effects of aneuploidy 16,20,[56][57][58][59][60][61][62][63][64][65][66][67][68][69] . We induced cytokinesis failure in these cells, thus generating tetraploid cells, which then spontaneously became highly aneuploid 70 .…”
Section: The Effect Of Aneuploidy On the Sensitivity To Sac Inhibitiomentioning
confidence: 99%
“…The high degree of plasticity of the MT network relies on the nucleation and polymerization/depolymerization of individual MT filaments. When the regulation of MT dynamics is disrupted, it causes pathological disorders such as cancer (Schukken et al, 2020) and neurodegenerative diseases (Kounakis and Tavernarakis, 2019). Therefore, understanding the molecular mechanism of MT dynamics is important for developing an effective treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, aneuploidy itself has also been observed to induce substantial tumor suppressive stresses 10,22,23 . Aneuploid cells have increased metabolic requirements [24][25][26][27][28][29] , display high levels of senescence 23,[30][31][32][33] , exhibit significant genomic instability 34,35 , and are sensitive to compounds that interfere with protein folding and turnover 28,[36][37][38] . Aneuploidy-associated stresses may be caused by the deregulation of gene expression, which leads to the imbalanced production of key cellular proteins.…”
Section: Introductionmentioning
confidence: 99%